0905 Obstructive Sleep Apnea In Pediatric Patients With Early Onset Scoliosis. (27th May 2020) - Panek, D; MacKintosh, E; DelRosso, L; Ruth, C; White, K; Redding, G
Abstract: Introduction: Early onset scoliosis (EOS), defined as curvature of the spine >10 degrees with onset before 10 years of age, is associated with increased rates of restrictive lung disease, pain, and other factors that increase risk of poor sleep. We compared the polysomnographic findings of children with EOS to those of children without EOS. We postulated that children with EOS would have a higher rate of OSA than patients without EOS, and differences in sleep stage distribution, arousals, and limb movements. Methods: Single-center retrospective chart review performed on 58 subjects with EOS (ages 1-17yr) who underwent PSG from 2003-2019; comparison group of 58 subjects without scoliosis who underwent diagnostic PSG was chosen consecutively (ages 1-18yr). Polysomnographic parameters compared include: sleep stage distribution, arousal index (AI), obstructive/central AHI, mean and nadir oxygen saturation in REM/NREM, and periodic leg movement index. All p-values were adjusted for multiple comparisons. Results: There was no difference in age or sex distribution between the two groups, though subjects with EOS had lower BMI than those without EOS (median 16.3 (IQR 14.7-19.3) vs. 17.5 (IQR 16.2-21.6), p=0.019). 84% of subjects with EOS had OSA, compared to 66% without EOS. Subjects with EOS and OSA had higher obstructive AHI than the OSA group without EOS, and longer duration of hypopneas. There was no significant difference in sleep stage distribution, AI, or PLMI. Conclusion: Of pediatric patients referred for polysomnography at our institution, those with EOS had a higher rate of OSA, more severe OSA where present, and lower BMI. We advocate for routine polysomnography for children with EOS due to the high risk of OSA amongst those tested, and further study to better understand the pathophysiology of sleep disordered breathing in this population. Support: This project is supported by the Health Resources and Services Administration (HRSA) of the US Department of Health and Human Services under grant #T72MC00007/University of Washington Pediatric Pulmonary Center/PI: Redding. The content and conclusions are those of the author and should not be construed as the official position or policy of, nor should any endorsements be inferred by HRSA, HHS or the U.S. Government.